Inhibition of MUC1 exerts cell-cycle arrest and telomerase suppression in glioblastoma cells - Kim, Sojin (Sci Rep, 2020)
Mucin 1 (MUC1) is a transmembrane glycoprotein involved in tumorigenesis of diverse cancers. However, the role of MUC1 in glioblastoma (GBM) has not yet been fully explored. In this study, the anticancer mechanism of MUC1 suppression in GBM was investigated. The expression level of MUC1 was analyzed in human glioma and paired normal brain tissues. MUC1 was overexpressed in GBM and was negatively associated with overall survival. Moreover, we silenced MUC1 to investigate its effect in GBM cell lines and found that knockdown of MUC1 inhibited cell proliferation and resulted in cell cycle arrest at G1 phase. MUC1 silencing decreased the phosphorylation of RB1 and increased the expression of CDKN1B. Gene set enrichment analysis showed that a series of genes related to cell cycle, telomere maintenance and transforming growth factor Beta (TGF-β) signaling in epithelial mesenchymal transition (EMT) were influenced by MUC1 knockdown. Notably, the reduced TERT expression levels combined with impaired telomerase activity and the switching of telomere maintenance mechanism to alternative lengthening of telomeres (ALT) were observed after MUC1 knockdown. Our results support the role of MUC1 in oncological process in GBM which can be developed as a therapeutic target for cell cycle control and telomere maintenance mechanism.